Experimental Study on Compaction Characteristics and Mechanical Behavior of Crushed Rock Masses - Xiaolou Chi; Qiang Fu; Ke Yang (Geofluids)
The compaction and consolidation process of a regenerated roof can be divided into two stages, namely, secondary fragmentation of crushed rock masses and pore structure adjustment. Therefore, the mechanical properties of the regenerated roof differs significantly from those of the primary roof. We performed confined compression tests of crushed mudstones and sandy mudstones using a self-developed compression testing apparatus. We studied the influence of the moisture content, compression ratio, particle size, and volume-based degradation on the compression and consolidation characteristics based on the microscopic morphology of the crushed rock masses. Further, the degrees of influence of these factors on the stability of the consolidated bodies were determined. Therefore, the influence mechanism of each factor on the compressive and shear strengths of the consolidated bodies was revealed. The results indicated that the compaction and consolidation of the crushed rock masses involved a constant adjustment of the contact and stress states of the rock masses. Under uniaxial compression and shearing, the consolidated bodies presented the features of ductile failure. The compression ratio and particle size were the most important influencing factors in the compressive and shear strengths of the consolidated bodies. Further, we carried out an orthogonal experiment and built a multivariate nonlinear regression model to quantitatively characterize the combined influence of these factors on the compaction characteristics of the crushed rock masses and the mechanical behavior of the consolidated bodies.